Agricultura familiar e seus impactos economicos e sociais no contexto da vida dos agricultores e agricultoras - Maurer, Alberto (2023)
This work analyzes the context of family farming in Brazil, a category that has been losing space in recent decades to non-family farming, which is easy to mechanize, generating concentration of income and production, according to data from IBGE (2017) family farming exploits only 23% of the agricultural area in our country, but it is responsible for 80% of national food production, in addition to supporting 77% of the population employed in the countryside. Given its importance, we saw the need to debate the reality of the municipality of Não-Me-Toque/RS, which lost 200 agricultural establishments in recent years, clarify which factors contributed to this scenario and what its consequences are for the families involved and local development. , relating to the role of the state and alternatives that can be suggested in the form of public policies aimed at this sector. To achieve our objectives, documentary research was carried out, followed by semi-structured interviews with local producers, which had a qualitative nature, followed by data analysis using the based discourse method. Analyzing the results, we noticed that the families' concerns are related to income, mainly the instability of prices, costs, climate, added to the lack of basic public policies that encourage staying in the countryside, many families migrate to paid activities in the urban perimeter, mainly young farmers who, without encouragement and autonomy, leave their properties without succession. Reflecting on this scenario, we suggest local policies aimed at crop diversification with investments guaranteed against crop failures, generating the possibility of greater income and guarantees for family investments, adding a lot to the development of municipalities.